A watermarking algorithm for color image based on YIQ color space and Integer Wavelet Transform - Qingtang Su; Xianxi Liu; Wenchao Yang (2009 International Conference on Image Analysis and Signal Processing, 2009)
Digital watermarking has been widely applied to solve copyright problems of digital media relating to illegal use or distribution. In the past few years, several gray-level image watermarking algorithms have been proposed, but few of them can be applied to color image. A digital watermarking algorithm for a color watermark embedded into a color host image, based on color space transform and IWT (Integer Wavelet Transform), is proposed. According to the Human Visual System peculiarity and quantizing the wavelet coefficient, Encrypted watermark is embedded adaptively into the luminance Y of the YIQ mode in IWT domain. The proposed algorithm allows extracting the watermark without the help of the original watermark and host image. Experimental results show that the embedded watermark is invisible and robust against common image processing.